Estimation of the Daily Global Solar Radiation using RadEst 3.00 software-A Case Study at Low land Plain Region of Nepal - Poudyal, Khem N.; Bhattarai, Binod K.; Sapkota, Balkrishna; Kjeldstad, Berit (Journal of Nepal Chemical Society, 2013)
The RadEst 3.00 verson software estimates daily global solar radiation at low altitude plain area using meteorological parameters precipitation, maximum and minimum temperatures and solar radiation of Simara (Lat.27.15°N, Lon.84.98°E, and Alt.137m). Radiation is calculated as the product of the atmospheric transmissivity of radiation times radiation outside the earth atmosphere. The model parameters are fitted in two years data by iterative procedures. An accurate knowledge of solar radiation distribution in each particular geographysical location is crucial for the promotion of solar energy technology. The values estimated by the models are compared with measured radiation data. The performance of the model was evaluated using the statistical tools such as root mean square error (RMSE), mean bias error (MBE), Coefficient of Residual Mass (CRM) and coefficient of determination (r2). The empirical solar radiation models that showed better results using BC, CD, and DB and among them Modular DCBB is the best model for this location The finding coefficients of different models can be utilized for the estimation of solar radiation at the similar meteorological sites of Nepal. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9237 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 48-57 Uploaded date : 12/3/2013